THE ROLE OF PROSTATE-SPECIFIC ANTIGEN IN MONITORING AND THERAPEUTIC FOLLOW-UP IN PATIENTS WITH BENIGN PROSTATIC HYPERPLASIA - Ferati, Maltina; Papraniku, Egzona; Kostovska, Irena (Sciendo, 2025)
Introduction: Prostatic disorders, including benign prostatic hyperplasia (BPH) and prostate cancer, are common in men over 50. While prostate cancer contributes to significant morbidity, BPH is the most prevalent non-malignant condition. Prostate-Specific Antigen (PSA) is used not only for early cancer detection but also for monitoring BPH progression and response to therapy. Clinical biochemistry laboratories play a key role in interpreting PSA values within the clinical context to support treatment decisions. Methods: This retrospective study included 50 male patients (mean age 66.5 years) undergoing routine PSA testing at the Biochemical Laboratory of the Clinical Hospital in Tetovo. All patients had previously been diagnosed with BPH and were treated with Tamsulosin 0.4 mg and/or Dutasteride 0.5 mg. PSA levels before and after a 6 to 12-month treatment period were compared to assess therapeutic response. Results: Baseline PSA values ranged from 0.5 to 18 ng/ml (mean 4.2 ng/ml). After treatment, 70% of patients showed reduced or stable PSA levels, while 30% had increases that, in some cases, prompted clinical re-evaluation and imaging. PSA monitoring supported therapeutic adjustment where necessary. Conclusions: Biochemical monitoring of PSA provides valuable insight into BPH treatment response and disease progression. Laboratory-clinician collaboration is essential for individualizing patient care and guiding long-term management strategies.
Keywords: benign prostatic hyperplasia (BPH); laboratory medicine; monitoring; prostate-specific antigen (PSA); treatment response